Interaksi antar-alter: Bagaimana sistem Dissociative Identity Disorder (DID) bekerja sesuai norma? - Tajuddin, Ridho Hafizh; Mokhasonah, Ismatul; Alifia, Rahillah; Syifa, Miftakhul (Maliki Interdisciplinary Journal, 2026)
Dissociative Identity Disorder (DID) is characterized by a split in a single identity, making it appear as if a person has two or more distinct personality parts (alters). Misunderstandings about DID often lead to social stigma and discrimination, which hinders treatment. This article aims to explain DID in the hope of changing this negative stigma against sufferers. This research used a literature review method, collecting data from journals, scientific articles, and books. This article found that people with DID often lack self-control. Alters can behave according to norms if the alter who takes over possesses normative character traits, values, or behavioral patterns. Not all alters behave normatively, as each alter can have different traits or personalities. Ultimately, this article calls for further research to study how different parts of a person’s personality change and interact over time, as well as the brain’s role in creating distinct identities. Furthermore, studies that observe people with DID over the long term and utilize their personal stories can help us better understand how these identities are formed and the effectiveness of existing treatments.